Validation of Echocardiographic Measurements in Patients with Pulmonary Embolism in the RIETE Registry - Lyhne, Mads Dam; Bikdeli, Behnood; Dudzinski, David M.; Muriel-García, Alfonso; Kabrhel, Christopher; Sancho-Bueso, Teresa; Pérez-David, Esther; Lobo, José Luis; Alonso-Gómez, Ángel; Jiménez, David; Monreal, Manuel; the RIETE Investigators (TH Open, 2024)
Background In acute pulmonary embolism (PE), echocardiographic identification of right ventricular (RV) dysfunction will inform prognostication and clinical decision-making. Registro Informatizado Enfermedad TromboEmbolica (RIETE) is the world's largest registry of patients with objectively confirmed PE. The reliability of site-reported RV echocardiographic measurements is unknown. We aimed to validate site-reported key RV echocardiographic measurements in the RIETE registry.Methods Fifty-one randomly chosen patients in RIETE who had transthoracic echocardiogram (TTE) performed for acute PE were included. TTEs were de-identified and analyzed by a core laboratory of two independent observers blinded to site-reported data. To investigate reliability, intraclass correlation coefficients (ICCs) and Bland–Altman plots between the two observers, and between an average of the two observers and the RIETE site-reported data were obtained.Results Core laboratory interobserver variations were very limited with correlation coefficients >0.8 for all TTE parameters. Agreement was substantial between core laboratory observers and site-reported data for key parameters including tricuspid annular plane systolic excursion (ICC 0.728; 95% confidence interval [CI], 0.594–0.862) and pulmonary arterial systolic pressure (ICC 0.726; 95% CI, 0.601–0.852). Agreement on right-to-left ventricular diameter ratio (ICC 0.739; 95% CI, 0.443–1.000) was validated, although missing data limited the precision of the estimates. Bland–Altman plots showed differences close to zero.Conclusion We showed substantial reliability of key RV site-reported measurements in the RIETE registry. Ascertaining the validity of such data adds confidence and reliability for subsequent investigations.
Keywords: echocardiography; right ventricular function; validity; pulmonary circulation; reliability